Pengaruh Promosi dan Lokasi terhadap Keputusan Berkunjung di Museum Siwalima Ambon - Falaq, Muhammad; Sjukriana, Juke; Pariama, Deria Tedry Lourentia (Stupa, 2023)
The goal of this study was to see if Instagram promotion and location had a partial and simultaneous effect on the visit decision to Museum Siwalima Ambon. This study used a quantitative research method with a questionnaire instrument and sample of 100 visitors to the Museum Ambon Siwalima. This study has 3 variables: Instagram Social Media Promotion (X1), Location (X2), and Visit Decision (X3) (Y). This study’s analysis included statistical descriptive analysis, coefficient of determination, and simple linear regression using SPSS 24.0. The findings of this study show that factors X1 and X2 have a substantial influence on Y, with a significance level of less than 0.05. The results of the influence coefficients X1 and X2 on Y = 0.758 were then obtained, indicating that Social Media Promotion on Instagram and Location both had a strong influence on the visit decision to Museum Siwalima Ambon.